A research framework for virtual-reality neurosurgery based on open-source tools - Fiederer, Lukas D.J.; Alwanni, Hisham; Volker, Martin; Schnell, Oliver; Beck, Jurgen; Ball, Tonio (26th IEEE Conference on Virtual Reality and 3D User Interfaces, VR 2019 - Proceedings, 2019)
Fully immersive virtual reality (VR) has the potential to improve neurosurgical planning. However, there is a lack of research tools for this area. We present a research framework for VR neurosurgery based on open-source tools. We showcase the potential of such a framework using clinical data of two patients and research data of one subject. As first step toward practical evaluations, certified neurosurgeons positively assessed the VR visualizations and interactions using head-mounted displays. Methods and findings described in our study thus provide a foundation for research and development of versatile and user-friendly VR tools for improving neurosurgical planning and training.
CRIS-Team Scopus Importer:2023-09-13
Keywords: 3D imaging; Health informatics; Image segmentation; Imaging; Medical technologies; Virtual reality